Passionate enquiry and school development : a story about teacher action research - Dadds, Marion (London ; Washington, D.C. : Falmer Press, 1995)
This book presents a detailed study of the potential of action research in professional education. It depicts a primary school teacher's use of action research, through a series of school-based assignments, to improve her teaching and to develop herself as a person and a professional.
Includes bibliographical references
Keywords: Action research in education; Action research in education -- Case studies